Circumpolar Seabird Monitoring Plan. CAFF Monitoring Report No.17. - Irons, David; Petersen, Aevar; Anker-Nilssen, Tycho; Artukhin, Yuri; Barret, Robert; Boertmann, David; Gavrilo, Maria V.; Gilchrist, Grant; Hansen, Erpur S.; Hario, Martti; Kuletz, Kathy; Maloy, Mark; et al. (CAFF International Secretariat, 2015)
A circumpolar plan to monitor seabird populations, created by CAFF's CBird Expert Group as part of the marine component of CAFF's Circumpolar Biodiversity Monitoring Program.